Towards a safer world: the imperativeness of the educational philosophy of 3hs (2017)
This paper x-rayed how the educational philosophy of the 3H s could help to build a safer world. The theme humanistic philosophy in regards to building a safer world is worth critical study. The world has remained volatile and vulnerable with series of kidnapping, arm conflicts and unrest in the society which has affected the population. Education has been regarded as a basic component of human development and single most important means for empowerment and sustained improvement in all well being. 3Hs of Educational Philosophy which are Humane society, Human commonwealth, and Humanistic tendencies are highly imperative in combating and resolving the unrest and building a safer world. This study concluded that Nigerian educational system should tailored her educational philosophy using 3Hs will not only help in building rational human being that will contribute meaningfully to the development of the society but also in the building of a safer world. 3Hs could be seen as an alternative for building a safer world